Metabolic plasticity in the hygrophyte Moringa oleifera exposed to water stress. (18th August 2018) - Brunetti, Cecilia; Loreto, Francesco; Ferrini, Francesco; Gori, Antonella; Guidi, Lucia; Remorini, Damiano; Centritto, Mauro; Fini, Alessio; Tattini, Massimiliano
Abstract: Over the past decades, introduction of many fast-growing hygrophilic, and economically valuable plants into xeric environments has occurred. However, production and even survival of these species may be threatened by harsh climatic conditions unless an effective physiological and metabolic plasticity is available. Moringa oleifera Lam., a multipurpose tree originating from humid sub-tropical regions of India, is widely cultivated in many arid countries because of its multiple uses. We tested whether M . oleifera can adjust primary and secondary metabolism to efficiently cope with increasing water stress. It is shown that M . oleifera possesses an effective isohydric behavior. Water stress induced a quick and strong stomatal closure, driven by abscisic acid (ABA) accumulation, and leading to photosynthesis inhibition with consequent negative effects on biomass production. However, photochemistry was not impaired and maximal fluorescence and saturating photosynthesis remained unaffected in stressed leaves. We report for the first time that M . oleifera produces isoprene, and show that isoprene emission increased three-fold during stress progression. It is proposed that higher isoprene biosynthesis helps leaves cope with water stress through its antioxidant or membrane stabilizing action, and also indicates a general MEP (methylerythritol 4-phosphate) pathway activation that further helps protect photosynthesis under water stress. Increased concentrations of antioxidant flavonoids were also observed in water stressed leaves, and probably cooperate in limiting irreversible effects of the stress in M . oleifera leaves. The observed metabolic and phenotypic plasticity may facilitate the establishment of M . oleifera in xeric environments, sustaining the economic and environmental value of this plant.